Mining industry: innovations and prospects for the development of materials science II : selected peer-reviewed full text papers from the 8th International Scientific Conference on Innovations and Prospects of Development of Mining Machinery and Electrical Engineering (IPDME 2020) : selected peer-reviewed full text papers from the 8th International Scientific Conference on Innovations and Prospects of Development of Mining Machinery and Electrical Engineering (IPDME 2020), April 23-24, 2020, Saint-Petersburg, Russia - Maksarov, Vyacheslav V.; Gabov, Victor V.; Martyushev, Nikita V. (Key engineering materials,, 2021)
This volume contains the selected papers presented at the 8th international scientific conference on Innovations and Prospects of Development of Mining Machinery and Electrical Engineering (IPDME 2020, St. Petersburg, Russia, on April 23-24, 2020). Within the framework of the conference, at Saint Petersburg Mining University, there were special sessions on novel materials for mining tools and equipment, materials study and engineering, mineralogy, and ore treatment. All included reviewed papers cover various topics within the field of materials science and present valuable research results. Alloy, Coatings, Composites, Deformation, Laser Processing, Mechanical Properties, Mineralogy, Minerals Processing, Plasma Spraying, Polymers, Steels, Structure Formation, Surface Tension Materials Science, Building Materials, Mechanical Engineering.